Influence Of Soy Isoflavones On Plasma Isoflavone And Oestradiol Levels In Layer Chicken (Applied Biological Research, 2023)
This experiment was conducted to assess the effect of soy isoflavones (daidzein  and genistein) on oestradiol concentration in the blood plasma of layer chicken.  Group I birds were fed with regular standard maize-soybean meal based diet as  per BIS 2007 specification containing 22.5% soybean meal, group II with  standard layer diet without soybean meal (BIS, 2007) and group III was  supplemented with soy isoflavones enriched diet (0.5 g dried hypocotyl sprout of  soybean 100 g-1feed) for a period of 56 days. The levels of free isoflavones in  soybean meal and blood plasma derived through β-glucuronidase treatment  were quantified using liquid chromatography–mass spectrometry (LC-MS)  technique. The genistein levels were 2.89 ± 0.02,1.84 ± 0.13, and 3.25 ± 0.04 µg  g-1, while daidzein levels were 1.15 ± 0.26, 0.20 ± 0.03, and 2.40 ± 0.09 µg g-1,  respectively, in feeds of groups I, II, and III. The mean genistein and daidzein  content in blood plasma was found higher for group III birds compared to other  two treatment groups. After feeding trial, plasma concentration of oestradiol 17β  was estimated by using radioimmune assay (RIA) technique which was found  higher for group II (673.45 ± 7.69 pg mL-1) as compared to the group I (979.21 ±  12.57 pg mL-1) and III (314.23 ± 6.34 pg mL-1). The study showed that the higher  amount of isoflavones in feed could lower endogenous production of oestradiol  from ovaries.
Keywords: Daidzein; genistein; isoflavones; liquid chromatography-mass spectrometry; phytoestrogens